Proceedings. Tenth International Workshop on Database and Expert Systems Applications. DEXA 99 1999
DOI: 10.1109/dexa.1999.795143
|View full text |Cite
|
Sign up to set email alerts
|

An architecture for modular on-line analytical processing systems: supporting distributed and parallel query processing using co-operating CORBA objects

Abstract: During the last few years, On-Line Analytical Processing (OLAP) has emerged as a valuable tool for the analysis, navigation and reporting of hierarchically organized data from data warehouses. Still, it remains a challenging task to implement and deploy an OLAP system, since no standardized architecture exists, which describes the common components and functionality of OLAP systems. Additionally, the formal models in use disregard the need for easily implemented and clearly defined interfaces between these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Various architectures [7, 68, and 69] were proposed for the one dimensional enhancement of OLAP systems. But, the most relevant work in this integrated enhancement was done by [70]. The authors proposed architecture for the integrated enhancement of OLAP system.…”
Section: B Integrated Enhancement Of Olapmentioning
confidence: 99%
See 1 more Smart Citation
“…Various architectures [7, 68, and 69] were proposed for the one dimensional enhancement of OLAP systems. But, the most relevant work in this integrated enhancement was done by [70]. The authors proposed architecture for the integrated enhancement of OLAP system.…”
Section: B Integrated Enhancement Of Olapmentioning
confidence: 99%
“…Previously it has been identified that there is a strong need of integrating performance improvement and visualization enhancement techniques [17]. Furthermore by utilizing the work of [7], which lacked in the areas of visualization work of OLAP data, schema generation and cube processing, this paper work moved a step forward and introduced an advanced architecture for the integrated enhancement of OLAP by combining OLAP with data mining techniques in [70].…”
Section: F Comparison Of the Proposed Work With The Literature Reviewedmentioning
confidence: 99%
“…During the last few years, a lot of work has been done on the enhancement of OLAP particularly on its performance and visualization. Various architectures [6], [31], [32] were proposed for the enhancement of OLAP systems. At this point the question arise that why there is a need for conceptual model for combining enhanced OLAP and data mining?…”
Section: Proposed Conceptual Modelmentioning
confidence: 99%
“…The idea underlying the Class Point method is the quantification of classes in a program in analogy to the function counting performed by the Function Point measure. In the procedural paradigm the basic programming units are functions or procedures; whereas, in the object-oriented paradigm, the logical building blocks are classes, which correspond to real-world objects and are related to each other [1], [8]. In this paper, we explore the Class Point approach for estimating the size of OLAP systems based on design documentation.…”
Section: Introductionmentioning
confidence: 99%
“…A data warehouse is a relational database that usually contains historical data derived from multiple, heterogeneous and independent data sources [16]. Materialized views are views that improve query execution times by pre-calculating expensive joins and aggregation operations prior to execution of queries and storing the results at the data warehouse [7], [8]. This dramatically improves the response time of decision support queries.…”
Section: Introductionmentioning
confidence: 99%